PENYUSUNAN PROGRAM APLIKASI INVENTARISASI POHON DI JALAN KH. RD. ABDULLAH BIN NUH BOGOR - Bambang Sulistyantara; Heru Rahmatullah (Jurnal Lanskap Indonesia, 2012)
Road is a unit that must be completed, efficient, and attractive. It must have a circulation, a good interaction, and an exciting experience for the pedestrian. The road is also a place to plant trees. A line of trees can be planted on the roadside and median of road. Tree is a plant with woody stem and branch. Planting trees along of the road can provide a shelter and comfortable, reduce noise, and direct pedestrian path and vehicle path. Unfortunately, trees can arise some problems such as fallen trees and broken branche. The problem has happened at Abdullah bin Nuh street, Bogor City.In order to avoid and or minimize the risk of trees problem,it is needed to construct trees database in form of inventory application program. This research found a model of database application program forinventory of trees condition at Abdullah bin Nuh street. The advantage of program is that it can be applicated up to city scale and can record the number of trees up to 99.999. Beside, the program can be applicated for other cities in Indonesia.